2008
DOI: 10.1080/15419060802198587
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride Regulates Connexin43 in Skeletal Myoblasts In Vitro: Possible Involvement in Wnt/β-Catenin Signaling

Abstract: Gap junction channels composed of connexin43 (Cx43) are essential for normal myogenic differentiation and skeletal muscle regeneration. Here, the aim was to study whether lithium chloride (LiCl) could regulate Cx43 expression and gap junction channel function by mimicking the Wnt/b-catenin pathway in primary myoblasts. Cx43 mRNA expression in myoblasts was up-regulated in response to 5 mM LiCl. The enhanced Cx43 protein expression resulting from treatment with 5 and 10 mM LiCl for 24 h increased gap-junctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Wnt-3a as well as LiCl-induced GSK-3 inactivation stabilized and increased cellular levels of β-catenin leading to β-catenin-dependent TCF/LEF transcriptional activity in differentiating myoblasts, which is in agreement with previous reports [11, 56, 57]. In addition, over-expression of WT-GSK-3β in myoblasts confirmed direct inhibition of β-catenin-induced TCF/LEF transcriptional activity by GSK-3β.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Wnt-3a as well as LiCl-induced GSK-3 inactivation stabilized and increased cellular levels of β-catenin leading to β-catenin-dependent TCF/LEF transcriptional activity in differentiating myoblasts, which is in agreement with previous reports [11, 56, 57]. In addition, over-expression of WT-GSK-3β in myoblasts confirmed direct inhibition of β-catenin-induced TCF/LEF transcriptional activity by GSK-3β.…”
Section: Discussionsupporting
confidence: 92%
“…This notion is further supported by in vivo evidence revealing that markers of muscle differentiation and regeneration are inversely related to GSK-3β activity during skeletal muscle regrowth [10]. Of note is that pharmacological inhibition of GSK-3β activity by lithium (LiCl) has a more striking effect on myoblast fusion and myotube formation than IGF-I [8], which could be related to the ability of LiCl to mimic Wnt/β-catenin signaling [11, 12]. …”
Section: Introductionmentioning
confidence: 97%
“…Several studies have demonstrated that β-catenin interacts with Cx43 promoter regulating its mRNA expression (Xia et al, 2010; Du W et al, 2008; Zhai Y et al, 2002; Ai Z. et al, 2000; Van der Heyden et al, 1998). Analysis by western blot of nuclear protein extracts from hepatocytes supplemented with SAMe 1h after the second supplementation, showed decreased nuclear β-catenin levels (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Cx43 has been shown to be a downstream target of Wnt pathway and Wnt/b-catenin signaling pathway in many cell types, including ovarian endometrioid adenocarcinomas (OEAs) and osteoblasts [36][37][38]. In mammary epithelial cells, Wnt-3a has been shown to up-regulate the expression of Cx43 gene and phenotypically increased transepithelial resistance across the cell monolayer [39].…”
Section: Discussionmentioning
confidence: 99%